2020
DOI: 10.1021/acs.jpcb.0c00266
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Effect of Environment on Excitation Energy Transfer in Photosynthetic Light-Harvesting Systems

Abstract: In recent years, two-dimensional (2D) electronic spectroscopy experiments prove that the excitation energy transfer (EET) in photosynthetic light-harvesting systems presents long-lived electronic quantum beating signals. After being discovered in the light-harvesting system, the quantum coherence effect has aroused widespread discussion. To illustrate the EET process in the Fenna–Matthews–Olson (FMO) and phycocyanin 645 (PC645) complex, the local protein environment is often thought to be the same; however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…To get rid of this reverse excitation transfer, site 6 needs to quickly transfer the excitation energy to other sites. According to our previous research, 38 when site 6 is initially excited, the strongly coherent oscillations first occur between site 6 and site 5, and then the excitation energy is gradually transferred to site 4, site 7, and finally to site 3. By the analysis of the research results, we find that BChl 6 is strongly coupled to BChl 5, BChl 4, and BChla 7.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To get rid of this reverse excitation transfer, site 6 needs to quickly transfer the excitation energy to other sites. According to our previous research, 38 when site 6 is initially excited, the strongly coherent oscillations first occur between site 6 and site 5, and then the excitation energy is gradually transferred to site 4, site 7, and finally to site 3. By the analysis of the research results, we find that BChl 6 is strongly coupled to BChl 5, BChl 4, and BChla 7.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Aghtar et al suggested that environmental fluctuation has an important effect on spectral density. Besides, extensive investigations have been carried out to study the robustness of the FMO complex with fluctuations in the surrounding protein environment, showing that the thermal fluctuation can enhance the EET by the so-called environment-assisted quantum transport.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, the eighth BChl pigment has also been newly resolved in the FMO protein that lies perpendicular to the plane of the other seven BChls [17,18]. Notably, FMO complex is a homotrimer of three ≈ 40 kDa monomer that possesses C3 symmetry whereby three copies of each subunit of seven BChl a chromophores bind together to the eighth BChl a pigment [16,19,20]. Due to close packing of BChl a pigments in each monomer subunit, the excited electronic states of FMO complexes are delocalized over multiple pigments.…”
Section: Introductionmentioning
confidence: 99%
“…Due to close packing of BChl a pigments in each monomer subunit, the excited electronic states of FMO complexes are delocalized over multiple pigments. The previous research in this field is mainly focused on developing and testing new computational and experimental methods for a better understanding of the delocalization of excited states over multiple pigments and the unfolding of the relationship between atomic structure and absorbance along with the fluorescence spectra [19,20]. Owing to the rotational symmetric of the monomer subunit of FMO trimer around the symmetry axis, there are two types of FMO complex structures widely analyzed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The dissipative excited state dynamics of molecular aggregates is often treated by separating the relevant system from an environment [1,2]. The latter is usually identified with a thermal bath of low-frequency modes of the surrounding molecular matrix, such as a protein scaffold [3][4][5], but can also comprise intramolecular vibrational modes of monomers in the aggregate [6][7][8][9][10][11]. In the "Hierarchical Equations of Motion" (HEOM) method all nuclear degrees of freedom are attributed to the environment [12], and all orders of perturbation theory with respect to their interaction with the system built from purely electronic components are taken into account at least in principle [13].…”
Section: Introductionmentioning
confidence: 99%